Nanodiamond‐Embedded p‐Type Copper(I) Oxide Nanocrystals for Broad‐Spectrum Photocatalytic Hydrogen Evolution. Issue 4 (30th November 2015) - Lin, Zhaoyong; Xiao, Jun; Li, Lihua; Liu, Pu; Wang, Chengxin; Yang, Guowei
Abstract : Copper(I) oxide (Cu2 O) is an attractive photocatalyst because of its abundance, low toxicity, environmental compatibility, and narrow direct band gap, which allows efficient light harvesting. However, Cu2 O exhibits poor photocatalytic performance and photostability because of its short electron diffusion length and low hole mobility. Here, it is demonstrated that nanodiamond (ND) can greatly improve the photocatalytic hydrogen evolution reaction (HER) of the p‐type photocatalyst Cu2 O nanocrystals by nanocomposition. Compared with pure Cu2 O nanocrystals, this composite shows a tremendous improvement in HER performance and photostability. HER rates of 100.0 mg NDs‐Cu2 O nanocrystals are 1597 μ mol h − 1 g − 1 and 824 μ mol h − 1 g − 1 under the simulated solar light irradiation (AM 1.5, 100 mW cm −2 ) and visible light irradiation (420–760 nm, 77.5 mW cm −2 ), respectively. The solar‐to‐hydrogen conversion efficiency of this composite is 0.85%, which is nearly ten times higher than that of pure Cu2 O. The quantum efficiency of the composite is high, with values of 0.17% at λ = 780 nm and 0.23% at λ = 850 nm . The broad spectral response of ND provides numerous carriers for the subsequent reactions. The electron‐donating ability of ND and suitable band structures of the two components promote electron injection from ND to Cu2 O. These results suggest the broad applicability of ND to ameliorate the photoelectric properties of semiconductors. Abstract : The use of nanodiamond to improve the photocatalytic hydrogen evolution reaction of Cu2 O by nanocomposition is demonstrated for the first time. Compared with pure Cu2 O, this nanocomposite shows a tremendous improvement in performance. It is also established that the electron‐donating ability of nanodiamond, and the suitable band structures of the two components enhance electron injection from nanodiamond to Cu2 O.